America's Founding Charters: Primary Documents of Colonial and Revolutionary Era Governance 232 (Jon L. Wakelyn ed. 2006) (Concessions and Agreements, Jan. 11, 1664) - (:unkn) unknown (My University, 1664)
All inhabitants and freemen of Carolina above seventeen years of age and under sixty shall be bound to bear arms and serve as soldiers whenever the grand council shall find it necessary."
Keywords: MILITIAS